THE USE OF WIKI WEBSITE: A SOLUTION TO IMPROVE STUDENTS’ WRITING PERFORMANCE - Azhari, Defry (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
This paper aims at sharing merits of wiki as one of fruitful educational technology in facilitating students to improve their writing’s performance in language classrooms. In implementing, this paper recommends CBLM with the stages are combination of positive input from the previous study: (1) training of using wiki, (2) grouping the students, (3) drafting, (4) revising, (5) editing, and (6) publishing. The results reveal Wiki and its merits can encourage students to be independent learners because they are able to effectively participate and contribute in writing their essays by sharing ideas, editing, and supporting to each other. The teachers, especially in Indonesia, can implement wiki by using CBLM in all level of students. However, teachers must adjust and consider some important aspects before utilize it in the classroom depend on students’ need and classroom environment.